Strangulating Closed-Loop Obstruction: Sonographic Signs - Hollerweger, A.; Rieger, S.; Mayr, N.; Mittermair, C.; Schaffler, G. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: To evaluate different sonographic signs of strangulating closed-loop obstruction retrospectively.Materials and Methods: Over a period of approximately 10 years all documents, US scans and video clips of patients with strangulating intestinal obstruction were reviewed. The following sonographic signs were evaluated: akinetic bowel loops; echo-free luminal content; hyperechoic congestion of the mesentery; free peritoneal fluid; bowel wall thickening; signs of ischemia on color Doppler or contrast-enhanced US. Moreover, we looked for signs of bowel obstruction proximal to the closed loop and for the width of the strangulated segment.Results: The most often documented features of strangulating closed-loop obstruction were an akinetic bowel loop (94 %), a hyperechoic and thickened mesentery (82 %) and free peritoneal fluid (100 %). In 54 % of cases the luminal content was almost anechoic. In 76 % of patients bowel wall thickening and in 50 % signs of ischemia on color Doppler or contrast-enhanced US were documented. In 67 % small bowel dilatation proximal to the strangulated bowel segment was present. The width of the strangulated bowel loops was 2.86 cm on average.Conclusion: The akinetic bowel loops, hyperechoic thickening of the attached mesentery and free peritoneal fluid are typical for strangulating closed-loop obstruction. An anechoic luminal content is only visible in about half of the patients, but this eye-catcher can lead the investigator to the correct diagnosis. In about one third of patients no signs of bowel obstruction proximal to the strangulated loops are present. Dilatation of the strangulated loop may be absent or mild.
Keywords: abdomen; small bowel; ultrasound; ischemia/infarction; strangulation